A Tool for Modeling and Simulation of Computer Architectures Using Petri Nets - Cintra, Marcelo H.; Ruggiero, Wilson V. (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 1995)
The developments in the field of computer architecture, especially parallel systems, lead to the design of even more complex architectures, making it difficult to take decisions that would increase the performance of the system. In order to analyze objectively the advantages of different architectural choices, it is important to have modeling and analysis techniques and tools that can efficiently acquire data about the system's performance. Petri nets have been used successfully as a modeling tool for computer architectures. However, the analysis of the complex nets needed to model real systerns has become a lirniting factor for using Petri nets. To efficiently use Petri nets for modeling these complex systems, one needs powerful computer simulation tools. In this pape r we present the program RP_SIM, an object oriented tool for the simulation of Petri nets. We use this simulator to analyze a simple computer architecture model, showing the viability of the use of Petri nets, together with the tool presented, to model general computer architectures.